, , , , , . .

 

 

!

 

:

:

 

 

 

?

StudentHelp, , MS Word. , , antiplagiat.ru, etxt.ru advego.ru. StudentHelp , Word .


:


:

: . : 12.10.2012. : 2010. : 8. antiplagiat.ru: < 30%

():


( )2 = 2 2 + 2
( )3 = 3 32 + 32 3
2 - 2 = ( + ) ( - )
3 + 3 = ( + ) (2 - + 2)
3 - 3 = ( - ) (2 + + 2)
(+ + )2 = 2 + 2 + 2 +2 +2 +2
.
= +
: = -
() =
() =
(: ) = :
- = 1 :
: = O
.
O =O O
O O = O
O : = O : O
(O) = O
O = /
OO = O
(O) = O
.
1, 2, 3, , n-1, n
n-1 - n = d
d 蠠
2 = 1+ d
3 = 2 + d = 1 + 2d
n = 1 + d(n-1)
Sn = (1 + n) n = (21 + ( n-1) d) n
2 2
Sn 頠
.
d .
d > 0
d < 0 .
.
1, 2, 3, , n-1, n
n+1 / n = q
2 = 1 q
q - .
3 = 2 q = 1 q2
n = 1 q n-1

(q > 1)
Sn = n q - 1 = 1 (qn -1 : q 1)
q 1
(q < 1)
Sn = 1 (1 - qn)
1 - q


Sn = 1
1 - q
.
= 12 ={2 1, 2 1, z2 z1}

c c=O(2 - 1)2 +(2 - 1)2 + (z2 - z1)2

a = d

= c cc ccos j
cos j = 12 + 12 + z1z2
O12 + 12 +z12 O22 +22 + z22
2 = c c2
= 12 + 12 + z1z2

cc, 1 = 1 = z1
2 2 z2

^ , 12 + 12 + z1z2
.
(c u)? = u?
u ? = u? v u v?
v v2
(c)? = 0
(xn )? = n xn-1
(ax)? = ax ln a
( )? =
(sin x)? = cos x
(cos x)? = - sin x
(tg x)? = 1
cos2 x
(ctg x)? = - 1
sin2 x
(ln x)? = 1

(1 / )? = - 1
2
(O)? = 1
2 O
()? = 1
.
log = 񠠠
log 1 = 0
log = 1
log (m n) = log m + log n
log m = log m - log n
n
log m n = n log m
log n Om = 1 log m
n
log = log
log


sin2x + cos2x = 1
tg x = sin x
cos x
ctg x = cos x
sin x
1 + ctg2 x = 1
sin2 x
1 + tg2 x = 1
cos2 x
tg x ctg x = 1

sin (a b) = sina cosb cosa sinb
cos (a b) = cosa cosb sina sinb
tg (a b) = (tga tgb)
(1 + tga tgb)
ctg (a b) = ctga ctgb + 1
ctgb ctga

sina + sinb = 2 sin (a + b) cos (a - b)
      2
sina - sinb = 2 cos (a + b) sin (a - b)
      2
cosa + cosb = 2 cos (a + b) cos (a - b)
      2
cosa - cosb = - 2 sin (a + b) sin (a - b)
      2
tga tgb = sin (a b)
cosa cosb
ctga ctgb = sin (b a)
sina sinb
sin2a - sin2b = cos2b - cos2a =
sin (a + b) sin (a - b)
cos2a - sin2b = cos2b - sin2a =
cos (a + b) cos (a - b)

sina = O1 - cos2a
sina = tga
O1 + tg2a
sina = 1
O1 + ctg2a

cosa = O1 - sin2a
cosa = 1
O1 + tg2a
cosa = ctga
O1 + ctg2a

tga = sina
O1 - sin2a
tga = O1 - cos2a
cosa
tga = 1
ctga

ctga = O1 - sin2a
sina
ctga = cosa
O1 - cos2a
ctga = 1
tga

sina sinb = cos (a - b) - cos (a + b)
2
cosa cosb = cos (a - b) + cos (a + b)
2
sina cosb = sin (a + b) + sin (a - b)
2
tga tgb = tga + tgb
ctga + ctgb
ctga tgb = ctga + tgb
tga + ctgb
ctga ctgb = ctga + ctgb
tga + tgb

sin2a = 2 sina cosa
sina = 2 sin (a) cos (a)
cos2a = cos2a - sin2a =
= 1 - 2sin2a =
= 2cos2a - 1
tg2a = 2 tga
1 - tg2a
= 2
ctga - tga
tga = 2 tg (a/2)
1 - tg2 (a/2)
ctg2a = ctg2a - 1
2 ctga
= ctga - tga
2
ctga = ctg2 (a/2) - 1
2 ctg (a/2)
sin x = a
x = (-1)n arksin a + pn

cos x = a
x = arkcos a + 2pn

tg x = a
x = arktg a + pn

ctg x = a
x = arkctg a + pn

sin (p /2 - a) = + cosa
sin (p /2 + a) = + cosa
sin (p - a) = + sina
sin (p + a) = - sina
sin (3p/2 - a) = - cosa
sin (3p /2 + a) = - cosa
sin (2p - a) = - sina
sin (2p + a) = + sina
----------------
cos (p/2 - a) = + sina
cos (p/2 + a) = - sina
cos (p - a) = - cosa
cos (p + a) = - cosa
cos (3p/2 - a) = - sina
..................



90% antiplagiat.ru, etxt.ru advego.ru




* . , .